(3CSeGA GdQLGd GdPjf aj GdegPH ddTjQGRis - (3GHf TOGO , jhSa Hf QGaY Hf Jeje Hf YJHg GdCSOj GdehUdj, HgGA GdOjf CHh GdeMGSf,J (B632 (3g` s
(3ChdgG (B:s
(3GdbWH GdChd ef GdcJGH fPcQ GdCSeGA GdehOhYI ai cJGH GdegPH Ydi JQJjH CHhGHg GdN s
(3BNQgG (B:s
(3BNQ eG ajg jfJgi HChd cJGH GdTgGOGJ HGSe (B" (3CfLTI (B" s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B230 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B299s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B549 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B11 s
(3eUOQ GbJfGA GdCUd (B:s
(3hdi GdOjf LGQ Gddg (B(255) s
Keywords: (3GdJGQjNs